A novel non-invasive electromagnetic extendable intercalary endoprosthesis: a proof-of-concept study - Huang, Siyi; Yang, Jiake; Li, Xinyu; Tang, Xiaodong; Ji, Tao (Frontiers in Bioengineering and Biotechnology, 2024)
Femur and tibia are the most commonly affected sites for primary malignant bone tumors in children. The wide resection of the tumor frequently requires the physis to be resected. The normal growth of the unaffected limb will result in a significant limb length discrepancy at skeletal maturity. To compensate for this resulting LLD, different generations of extendible endoprostheses have been developed. Non-invasive extendable prostheses eliminate the need for surgical procedures and general anesthesia, enabling gradual and painless lengthening. Currently available non-invasive extendable prostheses focus on joint reconstruction, and no case series analysis of intercalary non-invasive extendable prosthesis has been reported. Therefore, we have designed a novel non-invasive electromagnetic extendable intercalary endoprosthesis. In vitro mechanical experiments and in vivo animal experiments were conducted. In vitro experiments have confirmed that the prosthetics can extend at a constant rate, increasing by 4.4mm every 10 minutes. The average maximum extension force during prosthetic elongation can reach 1306N. In animal in vivo experiments, the extension process is smooth and non-invasive, and the sheep is in a comfortable state. The in vitro and in vivo animal studies provide evidence to support the extension reliability, laying the foundation for future large-scale validation experiments.